Alcohol intake and brain structure in a multiethnic elderly cohort. - Gu, Yian; Scarmeas, Nikolaos; Short, Erica Eaton; Luchsinger, José A; DeCarli, Charles; Stern, Yaakov; Manly, Jennifer J; Schupf, Nicole; Mayeux, Richard; Brickman, Adam M (Clin Nutr, 2014)
BACKGROUND & AIMS: Evidence suggests that consuming light-to-moderate amounts of alcohol reduces the risk of dementia and is associated better cognitive function and less cardiovascular disease, relative to those consuming no or heavy alcohol. There are only minimal data on the association between alcohol and brain magnetic resonance imaging (MRI) markers. This study aimed to examine the association between alcohol and brain structure measured with MRI. METHODS: In this cross-sectional study, high-resolution structural MRI was collected on 589 multi-ethnic community residents of New York aged ≥65 with available alcohol intake assessments via a food frequency questionnaire. Total brain volume (TBV), white matter hyperintensity volume (WMHV), and presence of infarcts were derived from MRI scans with established methods. We examined the association of alcohol intake with these imaging markers using regression models adjusted for demographic, clinical, and vascular risk factors. RESULTS: Compared to non-drinking, light-to-moderate total alcohol (b = 0.007, p = 0.04) or wine (b = 0.008, p = 0.05) intake, but not beer or liquor intake, was associated with larger TBV. Further analysis showed a dose-response association between alcohol (p-trend = 0.03) or wine (p-trend = 0.006) and TBV. Overall, alcohol intake was not associated with WMHV or brain infarcts. CONCLUSIONS: Our study suggests that among older adults in the community, light-to-moderate alcohol intake, in particular wine, is associated with larger TBV. These findings suggest that light to moderate alcohol consumption is potentially beneficial for brain aging, but replication is needed.